Analysis of money management skills as a character building of responsibility and creativity in elementary school students - Sulistyowati, Prihatin; Sudarmiatin, Sudarmiatin; Atok, Rosyid Al (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Financial management skills are very important in life, so these skills must be trained from an early age so that when they grow up they become wise people who use money responsibly. This study aims to describe the results of the analysis of the ability of elementary school students to manage their money creatively and responsibly. This research method is descriptive qualitative. Data collection by survey by giving instruments in the form of questionnaires 12 questions for individuals and 1 question for groups. The research sample as the source is 80 public and private elementary school students in Malang city. Data analysis techniques using Miles and Huberman with data collection steps, data reduction, data presentation and data verification. Based on the results of the survey of the ability to manage finances in the aspect of utilizing pocket money for saving and entrepreneurship individually with group financial management obtained, it shows that there is not too much difference. In individual results, the majority of students have set aside pocket money to save and do small businesses but have not yet appeared well managed, in group results there is already a detailed planning of financial management for business but the calculation of capital and profit is not appropriate. Financial management skills in elementary school students still need more serious handling in order to increase more creative and responsible.